Separations, Sorting, and Cyclical Unemployment - Mueller, Andreas I. (American Economic Review, 2017)
This paper establishes a new fact about the compositional changes in the pool of unemployed over the US business cycle. Using microdata from the Current Population Survey for the years 1962–2012, it documents that in recessions the pool of unemployed shifts toward workers with high wages in their previous job and that these shifts are driven by the high cyclicality of separations for high-wage workers. The paper finds that standard theories of wage setting and unemployment have difficulty in explaining these patterns and evaluates a number of alternative theories that do better in accounting for the new fact. (JEL E24, E32, J31, J63, J64)